Preparação e caracterização de hidrogéis à base de quitosana com potenciais aplicações na agricultura - Natália Maria Borges Ladeira (2020)
Absorbent hydrogels are classified as three-dimensional structures made up of polymers that are capable of absorbing and releasing, in a controlled manner, large amounts of water, nutrients and ionic substances, without dissolving, when subjected to a crosslinking process. Biodegradable polymers of chitosan and derivatives have been studied as potential optimizers for drainage and water availability in the soil. In this work, carboxymethyl chitosan (CMC) was synthesized and subsequently chitosan and CMCbased hydrogels were prepared with diisocyanate crosslinkers in 6 mass proportions. CMC was characterized by spectroscopy in the infrared region, elemental analysis, X-ray diffraction, thermogravimetric analysis and zeta potential and the obtained product is less crystalline and more hydrophilic than chitosan. The hydrogels were characterized by spectroscopy in the infrared region, thermal analysis, scanning electron microscopy and subjected to swelling tests at different pHs and absorption of NPK fertilizers. The results confirmed the crosslinking of the polymer chains by identifying the formation of urea groups in the FTIR spectra and showed the difference in their structures before and after swelling. Chitosan hydrogels did not show significant water absorption, while CMC02 and CMC05 samples had a water absorption capacity of 60 g.g-1 . The NPK absorption tests showed that the CMC05 sample was able to absorb approximately 200mg of fertilizer per gram of hydrogel. The study presented is a good start for the development of hydrogels with potential biodegradability prepared through simple and fast methodologies and using water as a reaction solvent